The phonological significance of military terminology in English and Uzbek languages - Normatov , Haydar (The Lingua Spectrum, 2025)
The article highlights the distinctive linguistic traits and sound patterns that define these specialized vocabularies as it examines the phonological significance of military terminology in Uzbek and English. It looks at the ways that syllable patterns, intonation, and stress in phonetics contribute to the uniqueness of military terms in both languages. Additionally, the study explores how phonology transmits authority, accuracy, and urgency—all of which are critical in military communication. In order to create effective and useful language in military contexts, the article compares Uzbek and English military terminology, exposing linguistic and cultural differences. It also covers how the development of military terms and their phonological characteristics has been influenced by historical, social, and technological drivers. This research is especially pertinent for linguists, military professionals, and language learners, offering an improved comprehension of how sound patterns demonstrate the functional and cultural aspects of military terminology in different linguistic systems. The findings offer valuable insights into the interaction between a language and specialized fields, highlighting the significance of phonology in shaping effective communication in high-stakes environments.